Fisheries, chaos and ethics. A note on India status - Filipe, J. A.; Coelho, M. P.; Ferreira, M. A. M.; Selvarasu, A. (International Journal of Latest Trends in Finance and Economics Sciences, 2013)
Historically in the world, since last century,fish stocks of many species have been overexploited. A good management of fisheries became essential to permit the preservation of species. Managing fisheries got increasingly complex, once many interests, often contradictory, are always involved. Moreover, through time, political will has not been enough to change things in many places around the world and overexploitation has remained for many species. In India, with a strong population density in many coastal areas depending on fishing, the situation is very severe for many species and new requirements for preservation are now being tried. In literature, fisheries have been analysed in contexts of uncertainty. Chaos theory is one of the theories that have been used to explain fisheries. This work intends to represent a reflection about fisheries overexploitation,considering the utilization of chaos theory and the understanding of the related problems taking into account ethics setting. The India situation is showed.